The in vivo inflammatory and foreign body giant cell response against different poly(l‐lactide‐co‐d/l‐lactide) implants is primarily determined by material morphology rather than surface chemistry. Issue 10 (27th July 2018) - Lucke, Silke; Walschus, Uwe; Hoene, Andreas; Schnabelrauch, Matthias; Nebe, J. Barbara; Finke, Birgit; Schlosser, Michael
Abstract: Biomaterials can cause a chronic local inflammation called foreign body reaction, with formation of foreign body giant cells (FBGC) by monocyte/macrophage fusion. However, FBGC appearance and role for biomaterials with different physicochemical properties are not yet fully understood. This study aimed at examining FBGC and inflammatory cells after intramuscular implantation of poly(l ‐lactide‐co‐d/l ‐lactide) (PLA) as membranes and uncoated electro‐spun fiber meshes or meshes with a positively charged plasma‐polymer coating into rats. After 7, 14 and 56 days, CD68 + and CD163 + macrophages, T lymphocytes, MHC‐II + cells, FBGC, and nestin‐stained tissue area as regeneration marker were morphometrically analyzed. FBGC occurrence was primarily determined by material morphology, as their numbers for meshes were 10‐fold higher during acute and 50‐fold higher during chronic inflammation than for membranes but comparable between uncoated and coated meshes. CD68 + macrophages decreased around and within meshes, while CD163 + macrophages and MHC‐II + cells increased within meshes. T lymphocytes within meshes were higher for coated meshes, suggesting that the peri‐implant tissue immunological response is also influenced by surface chemistry. FBGC were predominantly CD68 + and CD163 −, and nestin‐stained tissue area was negatively correlated with CD68 + monocytes/macrophages numbers and positively correlated with CD163 + macrophages numbers, highlighting differing roles in FBGC formation and tissue regeneration. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 106A: 2726–2734, 2018.